Analysis of Slang in Mobile Legends Facebook Trading Account Posts and Comments - Syaiful Hamzah; M. Aprianto Budie Nugroho; Wulan Rahmatunisa (Darussalam English Journal (DEJ), 2025)
This study explores the use of slang words in the post and comment sections of the “Jual Beli Akun Mobile Legends Indonesia” Facebook community. The purpose of this research is to identify the types of slang and the types of meaning conveyed in the communication among users within this digital marketplace. Using a qualitative descriptive method, the data were collected through document analysis from 105 posts and 17 comments over the span of one week. The study applied Allan and Burridge’s classification of slang (Clipping, Acronym, Fresh and Creative, Imitative, and Flippant) and Leech’s theory of meaning (Conceptual, Connotative, Stylistic, and Affective). The findings revealed that Clipping was the most dominant slang type, indicating a preference for brevity and efficiency. Connotative meaning was also the most prevalent, showing how slang reflects not only linguistic function but also social and emotional context. The results suggest that slang in this online community is used not only to simplify communication but also to build shared identity, express sentiment, and reinforce group belonging. This study contributes to understanding how digital communities, especially those based on gaming and trading, develop and sustain their own informal linguistic norms. Types of Meaning